Are all transit stations equal and equitable? Calculating sustainability, livability, health, & equity performance of smart growth & transit-oriented-development (TOD). (September 2019) - Appleyard, Bruce S.; Frost, Alexander R.; Allen, Christopher
Abstract: Purpose: While "Smart Growth", Transit-Oriented-Development, and "Livability" have been around for years, little research has provided a framework to measure and understand their performance so we can realize key sustainability, livability, health, and equity outcomes. Procedures: In response, this paper builds on literature and practice to evaluate over 350 light rail stations throughout the US, using smart growth, livability, and Transportation/Land-use Coordination (TLC) principles. Using recently developed Livability and Smart Growth Equity calculators (http://bit.ly/SmartGrowthEquity ), and a smart growth/livability place-typology framework, this research assesses and grades "livability opportunity access" performance of these station areas along such key dimensions as regional/local access to jobs, services, transit, walkability. Using analysis of variance (ANOVA) methods, we show the significant associations between this livability access and the potential for realizing key quality-of-life benefits important for both individuals and society. But are all people able to equitably access these livability opportunities around transit so they can work towards realizing their desired quality of life? Findings: This study provides a unique evaluation of urban quality performance related to Transportation Land-use Coordination (TLC), "Smart Growth" and "New Urbanism. We find stations with higher levels of livability opportunity access to be significantly associated with key quality of life outcomes for individuals and society, such as lower rates of obesity, cardiovascular disease, asthma, driving, carbon emissions, and even lower poverty and unemployment. These higher-performing stations also have higher rates of walking, bicycling, transit use associated with lower household transportation costs which offset higher housing costs. Unfortunately, these stations are not socio-economically inclusive – in sum, all stations are not equal, or equitable. Using livability-opportunity-access-assessments with livability ethics, we recommend transportation and land-use agencies coordinate policies to provide equitable access to opportunities so all people can pursue and realize sustainability, livability, health, and equity outcomes for themselves and society. Highlights: Study provides a unique evaluation of urban quality performance and the equity "Smart Growth" & TOD. Performance determined by: 1) Opportunity Access; 2) Quality of life outcomes; & 3) social-equity of benefits. Higher Livability Opportunity Access is associated with lower rates of obesity, asthma, poverty and unemployment. Higher LOA is associated with higher rates of walking, bicycling, transit use, and lower driving and household transportation costs. Higher LOA stations are not socio-economically inclusive-therefore all stations are not equal, or equitable. Transport & LU agencies should coordinate policies using livability-opportunity-access & livability ethics/equity principles .